2022
DOI: 10.3802/jgo.2022.33.e51
|View full text |Cite
|
Sign up to set email alerts
|

Bone health after RRBSO among BRCA1/2 mutation carriers: a population-based study

Abstract: Objective Examine the risks of fractures and osteoporosis after risk-reducing bilateral salpingo-oophorectomy (RRBSO) among women with BRCA1/2 mutations. Methods In this retrospective population-based study in British Columbia, Canada, between 1996 to 2017, we compared risks of osteoporosis and fractures among women with BRCA1/2 mutations who underwent RRBSO before the age of 50 (n=329) with two age-matched groups wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Do Valle et al [14] conducted a retrospective populationbased study between 1996 and 2017 with 359 patients with BRCA1 and BRCA2 mutations who underwent RRBSO before the age of 50 without a cancer diagnosis. They concluded that while osteoporosis risk was higher in carriers of BRCA mutations, the risk of fracture was not.…”
Section: Discussionmentioning
confidence: 99%
“…Do Valle et al [14] conducted a retrospective populationbased study between 1996 and 2017 with 359 patients with BRCA1 and BRCA2 mutations who underwent RRBSO before the age of 50 without a cancer diagnosis. They concluded that while osteoporosis risk was higher in carriers of BRCA mutations, the risk of fracture was not.…”
Section: Discussionmentioning
confidence: 99%